Defense and counter-defense in rice–virus interactions - Jiaqi Qin; Ci Wang; Leqi Wang; Shanshan Zhao; Jianguo Wu (Phytopathology Research, 2019)
Abstract Rice viruses, known as “rice killer”, are vector-borne pathogens that cause severe disease and significant yield loss in rice production around the world. Rice virus disease is characterized by uncontrolled virus replication and the activation of host responses that contribute to pathogenesis. Underlying these phenomena is the potent suppression of rice antiviral responses, particularly the RNA silencing pathway and plant hormone pathways, which play vital roles in antiviral immunity. Classical rice virus disease control strategies include chemotherapeutics and use of disease resistance rice varieties. Here, we summarize recent advances in understanding the mechanisms behind the immune evasion and rice viral pathogenesis. Based on these mechanistic insights, we discuss how to combine different strategies for maintaining the effectiveness of rice resistance to viruses, and propose theoretical basis for the next generation of virus-resistant rice plants.